40 Jahre kernmagnetische Resonanz: Anwendung moderner Messmethoden auf stereochemische Probleme am Beispiel Brevicomin - Peter Bigler; Matthias Kamber (CHIMIA)
Development of modern techniques in NMR spectroscopy has been so rapid in recent years, that the spectroscopist now has a wide «spectrum» of informative methods at his disposal. The application of two selected pulse techniques to exo-brevicomin demonstrates the high power of modern NMR spectroscopy in solving stereochemical problems.